PENGEMBANGAN MEDIA ANIMATED PRESENTATION BERBASIS CANVA DALAM PEMBELAJARAN RELIGIUSITAS - Wulandika, Agustina Titis; Permana, Natalis Sukma (CREDENDUM: Jurnal Pendidikan Agama, 2021)
This research aims to determine the validity of Canva-based animated presentation media and assess the practicality of Canva-based animated presentation media in Religious Studies. The subjects of this study were 30 students of grade XI at Bonaventura Senior High School, Madiun. The data analysis techniques used in the study were qualitative descriptive analysis and qualitative descriptive analysis. The value analysis used the coefficient value from Aiken’s V. Aiken’s V is an agreement index of the average according to the items with indicators, and measurements using those items.The type of research is Research and Development (R&D) with the ADDIE steps; Analysis, Design, Development, Implementation, and Evaluation. Data collection methods use questionnaires tested by 2 expert media validators, 2 expert content validators, as well as small group tests and field trials. The results of the media expert validation test obtained a V index of 0.90 (very feasible criteria), and the score from the content expert resulted in a V index of 0.85 (very feasible criteria), indicating that the developed media meets the validity criteria. The results of the small group trial by 3 students obtained a score of 80.00, indicating very good criteria, and the results of the field trial by 30 students obtained a score of 78.77, also indicating very good criteria. The development of Canva-based animated presentation media in Religiosity Studies is declared feasible for use to support face-to-face and offline learning.